(NmE^TA |JN[TEJNA (B:s (Nw POISKAH EDINOJ TEORII STROENIQ wSELENNOJ (B: (NpER(B. (NS ANGL(B. /s - (NpARKER(B, (NbARRIs; (NmACARSKAQ(B, (No(B.(Ni(B.s; (NsMORODINSKIJ(B, (Nq(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1991)
(NbIBLIOGR(B. (NW KONCE KN(B.s
Keywords: (NtEORETI^ESKAQ FIZIKA s; (NtEORIQ OTNOSITELXNOSTI s; (NkOSMOLOGI^ESKIE PROBLEMY TEORII OTNOSITELXNOSTIs